LEARNING ENGLISH VOCABULARY USING KAMPUNG INGGRIS SOCIAL MEDIA ACCOUNT - Melati Nur Qurataini Zalzabilah (Dialectical Literature and Educational Journal, 2022)
Currently learning can be done vocabulary can use social media. Social media that are widely used by the younger generation today are YouTube and Instagram, there are lots of YouTube and Instagram accounts for learning English, one of which is Kampung Inggris. Students who want to learn English in an easy and accessible way can view content on social media that has been presented by Kampung Inggris. This study aims to determine the use of social media YouTube and Instagram in Kampung Inggris as a method of learning vocabulary at SMPN 06 Bekasi. This study uses a qualitative method. In this study, interviews with English teachers will be conducted to find out more about learning English using Instagram and YouTube social media from Kampung Inggris. Questionnaires are given to students regarding the use of Instagram and YouTube social media during vocabulary learning at school, observations are made by giving some questions to find out which social media is more often used by students and documentation of student learning activities. The results of this study found that 66,66% of students prefer learning through YouTube than Instagram. Social media YouTube and Instagram also provide positive benefits for students because they can increase learning motivation and increase students' vocabulary.